IMPLEMENTATION OF BUSINESS MODEL BASED ON ISLAMIC BUSINESS (Case Study in TRAC Sharia PT. Serasi Autoraya) - Wisnu Wijaya; Fajar Surya Ari Anggara (Islamic Business and Management Journal, 2018)
During this growth, human needs against product of goods and services has increased. It is demanding the company to be more active in developing his business. According to Central Bureau of Statistic (BPS), shows that transportation and warehousing sector has increased in the year 2017 is 5.41 %, this number is larger than the years 2016 to reach 5.20 %. The emergence of an increasing services company needed innovation in improving his business. TRAC Sharia as one of service business have the advantage that apply Sharia concept in its business. The purpose of this research is to know the business model TRAC Sharia and the application of business models TRAC based on Islamic business. This research uses qualitative descriptive research methods approach grounded. As for location of this research in the company of TRAC Sharia. In data retrieval, researcher using the technique observation, interview and documentation. In determining the sample of interviewees, the researcher uses a technique of probability sampling. The results of this research is the description of the business model TRAC Sharia is: customer segment, first through the concept of B to B, the second is a business that related with halal business; value propositions, the first transaction free from usury, the second cash back opportunity concept; channels, first doing socialization, second follow a variety halal event; customer relationship, visiting to the customer; revenue stream, the magnitude of rent is determined by the cost structure TRAC Sharia of the transport, maintenance & mudharabah; key resources include customer transport; key activities include offering the product to customer and take care of customer needs; key partnership includes Wardah, BMT Sidogiri & syariah financing; cost structure includes mudharabah, maintenance & operational. The application of business models TRAC Sharia based on Islamic business are: principle include a believe in way that God gave to who's defending his religion; motivation includes the concept transparency and free from haram elements; orientation includes the concept of cash back opportunity; work ethic include provide solutions to the customer in terms of transport with the concept of free usury; mental attitude includes free penalty but CSR funds; amanah includes conducting routine maintenance timely; human resources include standard salaries employee of TRAC Sharia; operations management include certification by MUI; financial management includes the transaction free from riba; marketing management covers the concept of socialization to the customer; human resource management includes standard grooming which includes women using hijab & employees understand sharia basic. From those results, researcher hope that TRAC Sharia improving business strategy based on the description of grouping strengths, weaknesses, opportunities and threats in its business. Next the researchers hope TRAC Shariah complement the Islamic value elements has not yet appeared in his business.